Pengaruh Pengaplikasian PGPR (Plant Growth-Promoting Rhizobacteria) terhadap Pertumbuhan dan Hasil Padi (Oryza sativa L.) Varietas Lokal di Desa Jatiluwih - ALVIANI, NI WAYAN DITA; PRADNYAWATHI, NI LUH MADE; ASTININGSIH, ANAK AGUNG MADE (Agrotrop : Journal on Agriculture Science; Vol 13 No 1 (2023), 2023)
Effect of PGPR ( Plant Growth-Promoting Rhizobacteria ) Application on Growth and Yield of Local Rice ( Oryza sativa L.) Varieties in Jatiluwih Village . The decline in local rice production in Jatiluwih Village needs to be overcome to meet the needs of the community, one method that can be used is the application of PGPR. This study aims to determine the differences in the effect of cultivation with PGPR application and without PGPR application on the growth and yield of local rice varieties and to find out which local rice varieties shows the highest yields. This study used a paired experiment that compared cultivation with and without PGPR application on four local rice varieties, namely Cicih, Cendana, Ketan and Mansur varieties. The results of the analysis showed that the application of PGPR in the cultivation of Jatiluwih local rice varieties was able to increase the average value of plant height, number of leaves per clump, leaf chlorophyll content, total number of tillers per clump, number of productive tillers per clump, panicle length, total grain per panicle, good grain per panicle and yield, respectively 1.66%, 16.89%, 5.97%, 18.79%, 15.65%, 11.54%, 25.65%, 30.55% and 10.53% when compared to cultivation without PGPR application. The Local varieties of Jatiluwih rice that showed the highest yield when compared between cultivation with PGPR application and without PGPR was the red rice variety Cicih, which increased by 19.27% ??from the previous 5.45 ton/ha to 6.50 ton/ha, while in Cendana variety only increased by 5.76%, Kentan variety increased by 11.33%, and Mansur variety increased by 5.57% after PGPR was applied.